2008
DOI: 10.1017/s0029665108008884
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetable intake and the risk of human cancer: epidemiological evidence

Abstract: Over several decades a number of epidemiological studies have identified the inverse associations between cruciferous vegetables and the risk of several cancers, including gastric, breast, colo-rectal, lung, prostate, bladder and endometrial cancers, via plausible physiological mechanisms. Although retrospective case-control studies have consistently reported inverse associations between the risk of these cancers and the intake of cruciferous vegetables and isothiocyanate-containing plants, current prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 67 publications
1
51
0
2
Order By: Relevance
“…3. More comprehensive reviews on various aspects of the topic are provided elsewhere [12,[29][30][31][32].…”
Section: Mechanisms By Which Broccoli May Prevent Cancermentioning
confidence: 99%
“…3. More comprehensive reviews on various aspects of the topic are provided elsewhere [12,[29][30][31][32].…”
Section: Mechanisms By Which Broccoli May Prevent Cancermentioning
confidence: 99%
“…Increasing daily intake of cruciferous vegetables is associated with reduced risk of certain cancers (Keck and Finley, 2004;Kim and Park, 2009;Tang et al, 2008;Wu et al, 2004). Chinese cabbage (B. rapa ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Cruciferous vegetables are good sources of a variety of nutrients and phytochemicals that might have excellent cancer-fighting properties. 5 Epidemiological studies have shown inverse associations between consumption of cruciferous vegetables and the risk of lung, colorectal, stomach, breast and other cancers, 6 but these studies are not all clearly consistent. Over the past two decades, a number of epidemiological studies have been carried out to investigate the association of cruciferous vegetables intake with prostate cancer risk, and most of them have reported inverse, but non-significant, associations; possibly as a result of a lack of statistical power in the individual studies.…”
Section: Introductionmentioning
confidence: 99%